The Translation of Taboo Utterances in Fifty Shade of Grey Movie Subtitle - Amanah Illahi; Nirwan Nirwan; Retno Ramadhina (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The purpose of this research is to find out analysis translation about taboo words in the movie. Taboo words is word or group of wourds that contain ambiguous or exactly inappropriate meaning. Taboo word may be not used or heard for under age. Furthermore, Taboo words might be very dangerous and inappropriate in our country, Indonesia. Whilst there are almost every western movie contains the taboo words. Maybe the purpose is to adjust with the plot or the theme of the story and to adapt with their culture or to make the movies looks natural. The movie transcript and subtitle that used is ‘Fifthy Shades of Grey”, because this movie is about a man named Grey who have a sadistic in sex, so that obviously, this movie contains so many taboo words. In this research, the methods that it used is observation and analysis of the transcript from English (SL) into Indonesia (TL), especially non-participant observation methods. Taboo words is devided into 10 types and it would be explained and there are some examples for each type. Overall, the purpose of this study is to analyse the types of taboo words and to find out how taboo words are translated from SL to TL.